2007
DOI: 10.1021/es071235e
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Copper Nanoparticles Causes Gill Injury and Acute Lethality in Zebrafish (Danio rerio)

Abstract: Increasing use of metallic nanomaterials is likely to result in release of these particles into aqueous environments; however, it is unclear if these materials present a hazard to aquatic organisms. Because some dissolution of metal particles will occur, it is important to distinguish effects of nanoparticulates from dissolved metals. To address this issue, acute toxicity of soluble copper and 80 nm copper nanoparticle suspensions were examined in zebrafish. The results demonstrate that nanocopper is acutely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
307
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 536 publications
(349 citation statements)
references
References 30 publications
28
307
3
6
Order By: Relevance
“…The lower toxicity of nCuO in freshwater may reflect its slower dissolution at low ionic strengths and Cu + 2 complexation in the presence of organic matter Garner and Keller, 2014;Griffitt et al, 2007;Blinova et al, 2010;Mortimer et al, 2010;Garner et al, 2015;Wang et al, 2011). Other studies indicate that the toxic effect observed from nCuO strongly correlates with the fraction of NP dissolved in aquatic media (Garner and Keller, 2014;Blinova et al, 2010;Aruoja et al, 2009).…”
Section: Aquatic Toxicity Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower toxicity of nCuO in freshwater may reflect its slower dissolution at low ionic strengths and Cu + 2 complexation in the presence of organic matter Garner and Keller, 2014;Griffitt et al, 2007;Blinova et al, 2010;Mortimer et al, 2010;Garner et al, 2015;Wang et al, 2011). Other studies indicate that the toxic effect observed from nCuO strongly correlates with the fraction of NP dissolved in aquatic media (Garner and Keller, 2014;Blinova et al, 2010;Aruoja et al, 2009).…”
Section: Aquatic Toxicity Studiesmentioning
confidence: 99%
“…Given their high density (8.96 g/cm 3 for nCu, 6.31 g/cm 3 for nCuO), Cu NPs settle out rapidly once they reach micron scale. nCu, with an isoelectric point (IEP) of pH 2.1, rapidly forms highly polydisperse micron-scale aggregates in simple salt solutions and natural waters (Conway et al, 2015a), both in the absence and presence of organisms (Griffitt et al, 2007). Rapid aggregation of nCu leads to fast sedimentation; for instance, only 20% of initial nCu mass was detected after 6 h in 10 mM NaCl at pH 7 .…”
Section: Environmental Fate Of Cu Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…The toxicological evidence of AgNPs is still lacking and the safety measurements for these nanoparticles have to be framed. The engineered nanomaterials comprise of numerous different physical forms and some of these materials including carbon nanotubes, carbon spheres called fullerenes (Zhu et al 2006) and nanoparticles made from metals (Griffitt et al 2007), metal oxides (Federici et al 2007) or composites made of several metals (King-Heiden et al 2009) have adverse effects on fish (Smith et al 2007). To study the aquatic toxicity, fish species has been widely used as an indicator of pollutant and they strongly respond to stress conditions.…”
Section: Introductionmentioning
confidence: 99%